Role of Non-Coding RNA of Human Platelet in Cardiovascular Disease - Inzulza-Tapia, Angela; Alarcón, Marcelo (Current Medicinal Chemistry, 2022)
Cardiovascular diseases (CVD) are the major cause of death in the world. Numerous genetic studies involving transcriptomic approaches aimed at the detailed understanding of the disease and the development of new therapeutic strategies have been conducted over recent years. There has been an increase in research on platelets, which are implicated in CVD due to their capacity to release regulatory molecules that affect various pathways. Platelets secrete over 500 various kinds of molecules to plasma including large amounts of non-coding (nc) RNA (miRNA, lncRNA or circRNA). These ncRNA correspond to 98% of transcripts that are not translated into proteins as they are important regulators in physiology and disease. Thus, miRNAs can direct protein complexes to mRNAs through base-pairing interactions, thus causing translation blockage or/and transcript degradation. The lncRNAs act via different mechanisms by binding to transcription factors. Finally, circRNAs act as regulators of miRNAs, interfering with their action. Alteration in the repertoire and/or the amount of the platelet-secreted ncRNA can trigger CVD as well as other diseases. NcRNAs can serve as effective biomarkers for the disease or as therapeutic targets due to their disease involvement. In this review, we will focus on the most important ncRNAs that are secreted by platelets (9 miRNA, 9 lncRNA and 5 circRNA), their association with CVD, and the contribution of these ncRNA to CVD risk to better understand the relation between ncRNA of human platelet and CVD.
Keywords: platelets